2013
DOI: 10.3389/fgene.2013.00035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure and relationships in indigenous cattle populations of Ethiopia and Korean Hanwoo breeds using SNP markers

Abstract: In total, 166 individuals from five indigenous Ethiopian cattle populations – Ambo (n = 27), Borana (n = 35), Arsi (n = 30), Horro (n = 36), and Danakil (n = 38) – were genotyped for 8773 single nucleotide polymorphism (SNP) markers to assess genetic diversity, population structure, and relationships. As a representative of taurine breeds, Hanwoo cattle (n = 40) were also included in the study for reference. Among Ethiopian cattle populations, the proportion of SNPs with minor allele frequencies (MAFs) ≥0.05 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
67
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 39 publications
16
67
10
Order By: Relevance
“…Similar to our results, F ST values of 1.2% (Dadi et al, 2008) and 1.1% (Zerabruk et al, 2011) from microsatellite markers, and 1.2% from a low-density taurine-derived chip (Edea et al, 2013), were reported among Ethiopian cattle populations. However, our F ST values were lower than those from previous studies of West African cattle breeds (6%; IbeaghaAwemu and Erhardt, 2005) and six African cattle breeds (4%; Gautier et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar to our results, F ST values of 1.2% (Dadi et al, 2008) and 1.1% (Zerabruk et al, 2011) from microsatellite markers, and 1.2% from a low-density taurine-derived chip (Edea et al, 2013), were reported among Ethiopian cattle populations. However, our F ST values were lower than those from previous studies of West African cattle breeds (6%; IbeaghaAwemu and Erhardt, 2005) and six African cattle breeds (4%; Gautier et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…A higher average F ST value (0.09) between Nellore and Northern Ethiopian cattle breeds was also observed (Zerabruk et al, 2011), compared with our finding of 0.07 for Ethiopian and Asian zebu. The lowest genetic differentiation and genetic distance observed among the Ethiopian cattle populations might be a result of their common ancestral origin and strong gene flow (Dadi et al, 2008;Zerabruk et al, 2011;Edea et al, 2013), a conclusion that is supported by our PCA and STRUCTURE analysis. The F ST estimates between Bangladeshi zebus and Ethiopian cattle were considered moderate (0.05 to 0.15), whereas estimates for Asian zebu and Hanwoo were very large (>0.25) (Wright, 1978).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Zebu cattle (Bos indicus) are the most common type of cattle in Ethiopia and renowned for their robustness under tough conditions (Edea et al, 2013). Moreover, they seem to have adapted to their environment very well, with reports indicating an ability to cope with dietary antagonists, such as tannins (Yisehak et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are anecdotal reports that these genotypes harbour great genetic diversity and adaptive traits that make them potentially valuable resources for breeding programmes in regions facing similar biological stresses, and in response to the present and future needs of livestock production (Van Arendonk, 2011;Acosta et al, 2013;FAO, 2015). Local Sanga genotypes can be used in various pure and cross breeding systems, helping farms to cope with projected management, market and climate scenarios in the future (Wilson, 2009;Edea et al, 2013).…”
Section: Introductionmentioning
confidence: 99%